Merengkuh Imaji, Melukis Liturgi: Sebuah Usaha Mengembalikan Fungsi Imajinasi Dalam Praktik Bernyanyi Kongregasional Melalui Teori Ontologi Trinitarian Supernaturalism John Jefferson Davis - Hansel Augustan (Indonesian Journal of Theology, 2020)
Imagination appears to be an inescapable aspect of the human order, one with the power to reveal meaning, grasp reality, animate feelings, and motivate people. Yet it can often go undertheorized and, thus, be undervalued.  This can be witnessed, for example, in the worship rituals of the Protestant church. Logocentrism and other various historical trajectories in this (broad) tradition have brought the church to a crisis of imagination. What an irony!—since worship is a bodily ritual that reveals the truest reality of the universe in sacramental ways. Therefore, this article attempts to revitalize and re-reveal the significance of the imagination, especially for believers in the context of Christian worship. Following the ontological theory of Trinitarian Supernaturalism as proposed by John Jefferson Davis, I explain how the imagination can become a vehicle that brings the congregation to interpret worship observances within a “holistic” ontology of reality. The implications will specifically address the practice of congregational singing as a performative activity that dominates worship rituals. With this elaboration, it is hoped that the congregation will be able to experience a sense of meaning that is holistic and authentic within its observance of worship.